Innovative therapies for malignant brain tumors: the road to a tailored cure - Giotta Lucifero, Alice; Luzzi, Sabino; Brambilla, Ilaria; Trabatti, Chiara; Mosconi , Mario; Savasta, Salvatore; Foiadelli, Thomas (Acta Biomedica Atenei Parmensis, 2020)
Background: Immune tolerance, immune escape, neoangiogenesis, phenotypic changes, and glioma stem cells are all responsible for the resistance of malignant brain tumors to current therapies and persistent recurrence. The present study provides a panoramic view of innovative therapies for malignant brain tumors, especially glioblastoma, aimed at achieving a tailored approach. Methods: PubMed/Medline and ClinicalTrials.gov were the main sources of an extensive literature review in which “Regenerative Medicine,” “Cell-Based Therapy,” “Chemotherapy,” “Vaccine,” “Cell Engineering,” “Immunotherapy, Active,” “Immunotherapy, Adoptive,” “Stem Cells,” “Gene Therapy,” “Target Therapy,” “Brain Cancer,” “Glioblastoma,” and “Malignant Brain Tumor” were the search terms. Only articles in English published in the last 5 years were included. A further selection was made according to the quality of the studies and level of evidence. Results: Cell-based and targeted therapies represent the newest frontiers of brain cancer treatment. Active and adoptive immunotherapies, stem cell therapies, and gene therapies represent a tremendous evolution in recent years due to many preclinical and clinical studies. Clinical trials have validated the effectiveness of antibody-based immunotherapies, including an in-depth study of bevacizumab, in combination with standard of care. Preclinical data highlights the role of vaccines, stem cells, and gene therapies to prevent recurrence. Conclusion: Monoclonal antibodies strengthen the first-line therapy for high grade gliomas. Vaccines, engineered cells, stem cells, and gene and targeted therapies are good candidates for second-line treatment of both newly diagnosed and recurrent gliomas. Further data are necessary to validate this tailored approach at the bedside.